Comparison of DSC‐MRI post‐processing techniques in predicting microvascular histopathology in patients newly diagnosed with GBM. Issue 2 (19th December 2012) - Essock‐Burns, Emma; Phillips, Joanna J.; Molinaro, Annette M.; Lupo, Janine M.; Cha, Soonmee; Chang, Susan M.; Nelson, Sarah J.
<x xml:space="preserve">Abstract</x> Purpose To evaluate which common post‐processing method applied to gradient‐echo DSC‐MRI data, acquired with a single gadolinium injection and low flip‐angle, most accurately reflects microvascular histopathology for patients with de novo, treatment‐naive glioblastoma multiforme (GBM). Materials and Methods Seventy‐two tissue samples were collected from 35 patients with treatment‐naive GBM. Sample locations were co‐registered to preoperative gradient‐echo dynamic susceptibility contrast (DSC) MRI acquired with 35° flip‐angle and 0.1 mmol/kg gadolinium. Estimates of blood volume and leakiness at each sample location were calculated using four common postprocessing methods (leakage‐corrected nonlinear gamma‐variate, non‐parametric, scaled MR‐signal, and unscaled MR‐signal). Tissue sample microvascular morphology was characterized using Factor VIII immunohistochemical analysis. A random‐effects regression model, adjusted for repeated measures and contrast‐enhancement (CE), identified whether MR parameter estimates significantly predicted IHC findings. Results Elevated blood volume estimates from nonlinear and non‐parametric methods significantly predicted increased microvascular hyperplasia. Abnormal microvasculature existed beyond the CE‐lesion and was significantly reflected by increased blood volume from nonlinear, non‐parametric, and scaled MR‐signal analysis. Conclusion This study provides histopathological support for both non‐parametric and nonlinear post‐processing of low flip‐angle DSC‐MRI for characterizing microvascular hyperplasia within GBM. Non‐parametric analysis with a single gadolinium injection may be a particularly useful strategy clinically, as it requires less computational expense and limits gadolinium exposure. J. Magn. Reson. Imaging 2013;38:388–400. © 2013 Wiley Periodicals, Inc.